Pelatihan Mengoptimalkan Product Google untuk Learning Management System video conference di SMK Insan Kamil Tartila Kab Tanggerang - Mochamad Adhari Adiguna, M.Kom; Bambang Wisnu Widagdo; Muhammad Anis (PT Triputra Sejahtera Prima, 2023)
Currently, the field of Information and Technologies is indispensable in many fields, including Education for learning due to the current pandemic that changes the way of learning in Indonesia, and even in the entire country in the world. To support video conference, google has google meet features. In addition to google meet, google also has features to be used for online learning, such as google classroom, google form, google spreadsheet and others. The use of these features is required by educational institutions and schools. Mastering the features allows teachers to conduct online learning optimally. This community service activity is intended for training participants to optimize their ability to use the Google features to be linked with online learning activities. The Institute for Research and Community Service of Pamulang University responds to concern for community problems, by holding Community Service activities in the form of